Efeitos do treinamento com exercícios resistidos nos fatores de risco para a síndrome metabólica - Vargas, Liziane da Silva de (2015)
The metabolic syndrome (MS) is characterized by the clustering of metabolic risk factors that can lead to cardiovascular diseases and Type 2 diabetes mellitus. Nowadays, health associations around the world indicate regular physical exercise in the prevention and in the treatment of this syndrome. However, only a few studies have investigated the isolated effects of resistance exercise training on metabolic syndrome. Thus, in Article 1, the purpose was to check the effects of 15 weeks of strength training (ST) on the inflammatory and hormonal profile of men with MS risk factors. In Article 2, the objective was to analyze the effects of strength training on the improvement of the MS components. For both articles, the study group consisted of 21 adult volunteers, male, aged between 40 and 64 years, with two or more risk factors for MS. There was an initial data collection and another one after 15 weeks of resistance exercise training. Anthropometric data, blood pressure, blood samples and food intake information were collected. The exercise protocol was performed three times a week for 15 weeks, with sessions of approximately one hour. These were composed of warm up, moderate to high intensity (55% to 80% of a Maximum Repetition) muscular resistance exercises and stretching. Data were analyzed using descriptive statistics. The Shapiro-Wilk test was performed to identify the data distribution and Student t test or Wilcoxon Rank test were used to verify the differences between pre and post-training results. Statistical significance was set at 5%. In Article 1, it was observed that the 15 weeks ST was effective in reducing IL-1, IL-6, IL-18, TNF alpha, IFN gamma, resistin, leptin, ghrelin and glucose levels, as well as increasing IL-10 and adiponectin levels. That meant positive changes in the inflammatory profile, hormonal and glucose metabolism without simultaneous loss of total body mass of the participants. In Article 2, it could be seen that ST was able to significantly reduce hip circunference, arterial blood pressure, body fat percentage and fasting glucose. These results demonstrate the improvement of the risk factors such as arterial blood pressure and glucose, which were normalized after ST. It was concluded that the ST was beneficial for the inflammatory and hormonal profiles, blood glucose and blood pressure of men with MS risk factors, even without total body weight loss. Thus, this protocol can be used as SM treatment strategy.